2007
DOI: 10.1677/erc-06-0020
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERβ palmitoylation in the inhibition of human colon cancer cell proliferation

Abstract: The cellular functions regulated by 17b-estradiol (E2) start after the hormone binds to its receptors (i.e., ERa and ERb). These act as ligand-dependent transcription factor transactivating target genes. In addition, E2 induces non-genomic actions, whose activation is triggered by a fraction of the ERs localized at the plasma membrane. Palmitoylation allows ERa to localize at the plasma membrane, to associate with caveolin-1, and, upon E2 stimulation, to activate rapid signals relevant for cell proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 58 publications
8
115
1
Order By: Relevance
“…Besides lipid modification, association of ERs to membrane and/or signalling proteins allows the activation of down-stream cascade signals important for E2 effects (12). In particular, we previously reported that the physical association between ERb, caveolin-1, and the un-phosphorylated form of p38 is present in DLD-1 cell line even in the absence of E2 (10). This prompted us to evaluate the effect of BPA on ERb molecular interactions with caveolin-1 and p38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides lipid modification, association of ERs to membrane and/or signalling proteins allows the activation of down-stream cascade signals important for E2 effects (12). In particular, we previously reported that the physical association between ERb, caveolin-1, and the un-phosphorylated form of p38 is present in DLD-1 cell line even in the absence of E2 (10). This prompted us to evaluate the effect of BPA on ERb molecular interactions with caveolin-1 and p38.…”
Section: Resultsmentioning
confidence: 99%
“…Equal amounts of soluble cell extracts were incubated with either 2.0 lg of anticaveolin-1 or anti-ERb antibodies. Cell lysis, immunoprecipitation, and SDS-PAGE were performed as previously described (10). Samples were probed with the indicated antibodies (10), and the reaction was visualized with indirect chemiluminescence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oestradiol receptor (ER) β is present in GCs (Hall et al 2001;Jacob et al 2006;Juengel et al 2006;Deroo et al 2009). Not only does ERβ interact with ERα, but it also regulates cell signalling cascades associated with E2 (Pettersson et al 1997;Koehler et al 2005;Galluzzo et al 2007;Zhao et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…75 Rapid non-genomic actions are the subject of much research worldwide and because uncertainty exists as to what exact cellular messaging cascades are involved in these non-genomic events, a wide variety of mediators have been examined. Whether or not classical estrogen receptors are involved in this rapid signalling is uncertain but a membrane bound receptor (which is dependant on palmitoylation for localisation) has been described 76 and is likely involved. It is not known whether ER β migration to the cell membrane accounts for these actions or whether an entirely different receptor isoform exerts the effects.…”
Section: Estrogen and Colon Cancermentioning
confidence: 99%